Textiles in a circular economy: An assessment of the current landscape, challenges, and opportunities in the United States - Schumacher, Kelsea A.; Forster, Amanda L. (Frontiers in Sustainability, 2022)
The production and consumption of textile products traditionally follows a largely linear (take, make, use, discard) economic model. Textiles are currently being produced in greater volumes than ever before, even after accounting for population growth, and unwanted products are discarded in mass quantities, most of which ends up in landfills or incinerated. This model causes serious social and environmental impacts and, thus, a transition to a more circular economic model – where materials and products are kept within the economy through reuse, repair, and recycling – is necessary. However, many challenges face a circular economy (CE) for textiles. Herein we discuss challenges and opportunities with the current textiles recovery system in the United States and outline activities and resources necessary to facilitate the transition to a CE in the U.S. Specifically, we describe the overarching need for collaboration, system harmonization, and data and information exchange. We further outline necessary actions in terms of standards development, labeling advancements, design characteristics, alternative business models for brands and retailers, end market development for recyclers, community engagement and educational programs, research and development, and the role of policy and regulation.